Danshen Modulates Nrf2-mediated Signaling Pathway in Cisplatin-induced Renal Injury - 曹思思;颜苗;侯振彦;陈莹;蒋云生;樊新荣;方平飞;张毕奎 (Current medical science, 2017)
Danshen, an efficacious agent for cardiovascular diseases, has been found to play an essential role in kidney injury. In the present study, the effect of Danshen on cisplatin-induced renal dysfunction was investigated in a mouse model. Danshen was administered to mice at a dose of 3 g/kg 4 days before and 3 days after cisplatin treatment. A single intraperitoneal injection of 20 mg/kg cisplatin was used to induce nephrotoxicity. The mice were sacrificed 72 h after cisplatin intoxication. Biochemical parameters including serum creatinine and blood urea nitrogen were analyzed. Histopathological changes of kidney tissues were detected using HE staining. Antioxidant enzymes（GSH-Px and SOD） and peroxidative product（MDA） were detected. Protein expressions of Nrf2 and its target genes including HO-1 and NQO1 were measured by Western blotting. The results showed that pretreatment with Danshen significantly reduced serum creatinine and blood urea nitrogen in the cisplatin-treated mice. Histopathological examination showed that Danshen mitigated the renal damage induced by cisplatin. Moreover, Danshen restored the activities of antioxidant enzymes（GSH-Px and SOD） and normalized the MDA contents in renal tissues. Western blotting revealed that Danshen enhanced the expressions of Nrf2 and its target genes in cisplatin-exposed mice. It was suggested that Danshen protects against the cisplatin-induced renal impairment in the mice, which is potentially associated with the upregulation of Nrf2-mediated signaling pathway.